Pegiat Perdamaian: Mengisi Rongga dalam Resolusi Konflik - Semy Arayunedya (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
Human beings are indeed made in God’s image as destined seekers of truth and in their multifaceted if fragile efforts to attain and communicate in both thought and action an element of correctness, certitude, consensus, coherence, commensurability, and fertile and liberating knowledge. Therefore, peace activists cannot be separated from the struggle to critically and introspectively apply the truth, with arguments ready to be tested.